Ultra-high evaporation rate 3D evaporator with vertical sheets based on full use of convection flow. (15th April 2022) - Peng, Lihua; Gu, Xiaobin; Yang, Haibin; Zheng, Dapeng; Wang, Pizhuang; Cui, Hongzhi
Abstract: Solar vapor generation technology is a promising strategy for clean energy-driven water treatments. The recently developed convection flow enhanced evaporator achieved a new breakthrough in the evaporation rate (over 10 kg m −2 ·h −1 ). However, the coupling of convection flow and evaporator is insufficient. The convection rate inside the evaporator is usually substantially lower than that outside, limiting the steam diffusion. In this study, a straightforward 3D evaporator with multi-vertical sheets was facilely obtained through 3D printing and assembly. The simulation results showed that the convection rate inside the evaporator is higher than that inside the inlet, and the humidity inside the evaporator is much lower than that inside the evaporator surface, resulting in enhanced vapor generation and diffusion. The ultra-high evaporation rate of 28.4 kg m −2 ·h −1 was finally achieved based on the full use of the convection flow. The correlation between convection flow and evaporation rate was linear, and the convection flow mechanism improving the evaporation rate was clarified. The cumulative mass change of the 3D evaporator in 8 h under an outdoor open system reached 70.7 kg m −2 . The associated desalinated seawater ion concentrations met the standards for healthy drinking water. Graphical abstract: Image 1 Highlights: ● A 3D evaporator was obtained through 3D printing and assembly. ● It presented a solar-to-vapor energy efficiency of 122.6% under 1.0 sun. ● The vertical sheets of 3D evaporator were well coupled with the convection flow. ● A high evaporation rate of 28.4 kg m −2 h −1 is accomplished at 1.0 sun and 6 m s −1 . ● The mechanism of convection flow enhancing evaporation rate is expounded.